Evaluation of a Functional Single Nucleotide Polymorphism of the SARS-CoV-2 Receptor ACE2 That Is Potentially Involved in Long COVID - Luo, Yu-Si; Luo, Lei; Li, Wei; Chen, Yan; Wu, Guo-Feng; Chen, Fang; Shen, Hu-Yan; Li, Hong-Man; Guo, Ming-Yang; Yin, Sha; Zhang, Ke; Cheng, Zhong-Shan (Frontiers in Genetics, 2022)
Since the occurrence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019, SARS-CoV-2 has led to a global coronavirus disease 2019 (COVID-19) pandemic. A better understanding of the SARS-CoV-2 receptor ACE2 at the genetic level would help combat COVID-19, particularly for long COVID. We performed a genetic analysis of ACE2 and searched for its common potential single nucleotide polymorphisms (SNPs) with minor allele frequency >0.05 in both European and Chinese populations that would contribute to ACE2 gene expression variation. We thought that the variation of the ACE2 expression would be an important biological feature that would strongly affect COVID-19 symptoms, such as “brain fog”, which is highlighted by the fact that ACE2 acts as a major cellular receptor for SARS-CoV-2 attachment and is highly expressed in brain tissues. Based on the human GTEx gene expression database, we found rs2106809 exhibited a significant correlation with the ACE2 expression among multiple brain and artery tissues. This expression correlation was replicated in an independent European brain eQTL database, Braineac. rs2106809*G also displays significantly higher frequency in Asian populations than in Europeans and displays a protective effect (p = 0.047) against COVID-19 hospitalization when comparing hospitalized COVID-19 cases with non-hospitalized COVID-19 or SARS-CoV-2 test-negative samples with European ancestry from the UK Biobank. Furthermore, we experimentally demonstrated that rs2106809*G could upregulate the transcriptional activity of ACE2. Therefore, integrative analysis and functional experiment strongly support that ACE2 SNP rs2106809 is a functional brain eQTL and its potential involvement in long COVID, which warrants further investigation.